Final report on the handicraft sector in Barbados, Grenada, Guyana, St Lucia, St. Vincent, Trinidad and Tobago - Wilson, Irwin (CEDP St. Michael, BarbadosBB, 1991)
Describes operations of various handicraft companies in selected CARICOM countries. Makes recommendations for their development in the areas of training of craftsmen, management, marketing, and shows need for financial, governmental and market information support. Outlines IDC's proposals for the development of the handicraft sector in Trinidad and Tobago. Lists titles dealing with crafts marketing. Contains country tables which explain the technical assistance needs of handicraft companies and show their state of readiness to export.